secA - tanA cos^2A
----------------- = --------------
secA + tanA (1 + sinA)^2
Answers
Answer:
secA-tanA
---------------- =LHS
secA+tanA
Step-by-step explanation:
Let secA=1/cosA
tanA=sinA/cosA
secA-tanA
----------------
secA+tanA
=(1/cosA-sinA/CosA)
-----------------------------
(1/cos A+sinA/cosA)
=(1-sinA)/cosA×cosA/(1+sinA)
=(1-sinA)
--------------
(1+sinA)
Multiplying by (1+sinA)/(1+sinA)
1-sin^2A
-------------
1+sin^2A
=cos^2A
----------------=RHS
1+sin^2A
Therefore Hence Proved
Hope it helps
Answer:
secA-tanA. (1/cosA)-(sinA/cosA)
......,............. =. ......................................
secA+tanA. (1/cosA)+(sinA/cosA)
= (1-sinA). 1+sinA
............. * .............
(1+sinA). 1+sinA
=1^2-sin^2 A. cos^2 A
..................... = ...................
(1+sinA)^2. (1+sinA)^2